Guiding approaches to studying Alzheimer's disease: a scoping review of community engagement, health communication, and implementation science research. - Yelton, Brooks; Workman, Lauren; Schaurer, Lauren; Riccardi, Nicholas; McCollum, Quentin; Belza, Basia; Ory, Marcia G; Thorpe, Roland J; Wheeler, Stephanie B; Trinh-Shevrin, Chau (Gerontologist, 2026)
Background and Objectives Alzheimer's disease and related dementias (ADRD) are a leading cause of death, affecting up to 57 million globally. Up to 45% of dementia cases could be prevented or delayed by addressing non-medical drivers of health (NMDoH). Community engagement, health communication, and implementation science are core areas of public health and important to consider when researching ADRD. However, these fields are often siloed, limiting the efficacy of ADRD prevention and intervention. This scoping review maps how researchers have incorporated models and theoretical frameworks from these fields specific to ADRD outcomes and with attention to NMDoH. Research Design and Methods We searched five social science databases, and articles were included if they were empirical, written in the English language, published 2010 forward, focused on ADRD or cognitive health, guided by or developed a framework, theory, or model, and addressed community engagement, health communication, or implementation science. Results We retrieved 2,428 articles, which were reviewed in multiple stages by five coauthors, resulting in a final sample of 32 articles. Most articles utilized published frameworks, models, or theories, while five were guided by author-developed approaches. Nine articles integrated two core areas, and only one article integrated all three. Discussion and Implications Increased integration of core areas and systematic application of theoretical frameworks are necessary to improve ADRD research with attention to NMDoH. Findings have the potential to inform training and mentorship opportunities for early-career researchers on best practices in interdisciplinary ADRD research, thereby improving community and population health outcomes.